Key Principles of Effective Licensing Regulation - Alimjonov Fayozbek (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Licensing regulation plays a critical role in balancing public interest protection with economic freedom and market efficiency. This chapter explores the key principles that underpin effective licensing frameworks, drawing from internationally recognized standards, particularly those developed by the Organisation for Economic Co operation and Development (OECD). The analysis covers core regulatory values such as proportionality, risk-based assessment, transparency, user-centric procedures, enforcement integration, legal integrity, adaptability, and stakeholder engagement. These principles are evaluated through both legal and economic lenses, including the public interest theory of regulation and concerns around regulatory capture.